Enhancing economic growth through financial industry agglomeration: Policy recommendations for the Guangdong-Hong Kong-Macao Greater Bay Area - Li, Feng; Awang, Azahan (Journal of Social Economics Research, 2025)
This study provides an in-depth empirical analysis of the determinants of regional economic growth in the Guangdong-Hong Kong-Macao Greater Bay Area, focusing on the roles of financial industry agglomeration, innovation, environmental regulation intensity, urbanization, and population density from 2007 to 2021. Utilizing a comprehensive panel dataset across 21 cities and employing advanced econometric techniques including the Method of Moments Quantile Regression this research uncovers robust evidence that financial development and innovation are consistent and powerful drivers of economic growth, regardless of city size or developmental stage. The findings indicate that, although advancement and innovation in the financial sector are universal drivers of economic performance, the impacts of environmental regulation and urbanization are more complex and highly heterogeneous across various quantiles of economic growth. Specifically, environmental regulation tends to promote growth in less developed cities but may impose constraints in more developed urban centers, whereas urbanization is more influential at early stages but diminishes as a city grows. The supported long-term cointegrating relationships between the variables also highlight that the regions involved require uniform, region-specific measures to maintain balanced, sustainable, and innovation-driven growth. These findings contribute to existing research in regional economics and offer transparent, applicable policy insights for decision-makers aiming to facilitate inclusive and resilient urban growth within one of China’s most vibrant metropolitan areas.